Ergonomi mengoptimalkan ruang kerja laboratorium kesehatan - amaliah, aisyah (Jurnal Pendidikan Kesehatan (e-Journal), 2025)
In an era of continuous development in the healthcare field, health laboratories are not just an additional component, but have become an integral entity that plays a crucial role in the healthcare system. The function of the laboratory is not only limited to providing critical information for disease diagnosis, but also the base of scientific research and routine monitoring of patient health conditions. In this context, it is important to recognize that the operational success of a health laboratory does not solely lie in the sophistication of the equipment and analytical methods used, but is also highly dependent on the understanding and implementation of ergonomic factors that affect the working environment of the health professionals in it. Ergonomic factors in health laboratories involve various elements, ranging from workspace design, equipment arrangement, to the safety policies implemented. Optimal workspace design not only includes aesthetic aspects, but also pays attention to comfort and efficiency in carrying out daily tasks. Equipment arrangement, including the placement of analytical tools and medical instruments, also plays an important role in creating a smooth and efficient workflow